21st Century Competencies in Light of the History of Integrated Curriculum - Drake, Susan M.; Reid, Joanne L. (Frontiers in Education, 2020)
Integrated or interdisciplinary curriculum (IC) is an effective and relevant way to teach the 21st century competencies and to apply the transdisciplinary skills necessary for solving complex global problems. We review the underpinnings of both traditional and progressive education and past periods of implementation of IC in order to understand its history. Multiple definitions of IC are identified on a continuum. Reasons to dismiss the continuum are also offered. Two periods when IC was implemented in a consistent way in the United States are explored: the progressive era from 1919 to 1955, and the late 1980s and early 1990s. Similarities in each era are identified such as progressive principles of teaching and learning. Differences are also considered in basic assumptions held by curriculum developers of the day with the 1980s and 1990s lacking the 1930s deep social purpose of teaching for a democratic society. The socio-political context is visited to understand the beginnings and endings of these eras. The current educational context is then viewed from a global context. We see a landscape in which accountability and disciplines are counterbalanced by a global redefinition of what’s worth knowing and a shift toward interdisciplinary competencies/skills/capabilities, well-being and teaching the whole child. Indeed, this is happening in places around the planet such as Finland. The ideas are reminiscent of the 1930s progressive movement—a time of experimentation when student interests and needs more than disciplinary content shaped an IC. We propose that the current global conversation can offer conceptual cohesion to encourage and support the implementation of IC and can act as a proxy for the Progressive Education Association that guided practitioners from 1919 to 1955.